Industrial training report: Baker Hughes Sdn Bhd - Shahrin, Shahzmeera (Universiti Teknologi MARA, Perlis, 2024)
I began my six-month industrial training with Baker Hughes Sdn Bhd, a prominent global company that offers comprehensive oilfield products, services, and digital solutions for the energy industry. Baker Hughes is widely recognised for its unwavering dedication to innovation, sustainability, and safety, which has led to significant progress in technology and operational excellence on a global scale. As an Indirect Tax Intern in the Finance department at Baker Hughes, my role focuses on supporting the LATAM team. My responsibilities include preparing and filing indirect tax returns, maintaining and organizing tax records, analyzing financial data for accurate tax reporting, and identifying discrepancies in financial records. This hands-on experience in tax compliance, data analysis, and audit support is invaluable for understanding indirect taxes and their applications across different countries. Additionally, the internship offers opportunities for skill development in data analysis, problem-solving, and understanding the intricacies of the oil and gas industry's interaction with tax regulations. Building professional connections and participating in industry events further enriches this experience, providing insights and exposure to best practices in tax compliance and auditing. Baker Hughes exhibits notable strengths, such as its extensive training programs and a diversified workforce. However, the company faces weaknesses like inconvenient work hours and an increased workload. The company has opportunities for growth through strategic partnerships and acquisitions and expansion in emerging markets. Conversely, it faces threats from market instability and competitive pressure. To leverage its strengths, Baker Hughes effectively penetrate emerging markets by leveraging its diversified workforce and mitigate the effects of market instability by utilizing its extensive training programs. Additionally, improving work-life balance through strategic partnerships and boosting competitive advantage through workforce efficiency are essential strategies for maintaining a competitive edge.